Comparative Assessment of Imaging Modalities in Biliary Obstruction (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Complete assessment of biliary obstruction requires the use of various imaging modalities to confirm the presence, level and cause of obstruction which can help in treatment planning. Commonly used procedures include Ultrasonography (USG), Computed Tomography (CT) and Magnetic Resonance Cholangiopancreatography (MRCP).Objective: To determine the accuracy, sensitivity and specificity and to compare the diagnostic accuracy of USG, CT scan and MRCP in assessing the level and cause of obstruction in patients with obstructive jaundice.Materials and Methods: This cross sectional descriptive study in 50 patients who presented in the department of Radiology and Imaging, Combined Military Hospital (CMH), Dhaka with symptoms and signs of obstructive jaundice above the age 20 years was carried out during the period from 01 October 2012 to 30 April 2013. The accuracy, sensitivity and specificity of each modality in assessing the level and cause of obstruction were determined.Results: MRCP detected level of obstruction in 100%, CT scan in 95.8% and USG in 90% cases. For detection of cause of obstruction, MRCP had the highest sensitivity (96.2%); followed by CT scan (88.4%) and USG (62.5%). The diagnostic accuracy for detection of cause of obstruction was the highest for MRCP (93.1%); followed by CT scan (89.8%) and USG (66%).Conclusion: MRCP has highest diagnostic accuracy and sensitivity by detecting the level and cause of obstruction most accurately.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 10-13